Functional Magnetic Resonance Imaging Correlations Between Fatigue and Cognitive Performance in Patients With Relapsing Remitting Multiple Sclerosis - Iancheva, Dessislava; Trenova, Anastasya; Mantarova, Stefka; Terziyski, Kiril (Frontiers in Psychiatry, 2019)
The correlation between fatigue and cognitive performance in Multiple sclerosis (MS) is well reported, but the intimate mechanisms of the fatigue impact on cognition are not fully defined yet. The aim of this study is to investigate blood oxygen level dependent (BOLD) activations in relapsing-remitting MS (RRMS) patients with and without cognitive dysfunction and the impact of fatigue on cortical activations. Forty-two patients with RRMS were enrolled in the study. Cognitive functioning was assessed by Symbol Digit Modalities Test (SDMT) and Paced Serial Addition Test (PASAT). Cut –off point of a total score of 55 on the SDMT was used to divide the patients in two groups: cognitively impaired (CI) – SDMT score equal to or below 55 points and cognitively preserved (CP) - SMDT score above 55 points. Fatigue was assessed by the Modified Fatigue Impact Scale (MFIS). All Participants were assessed with Beck Depression Inventory (BDI). The fMRI scanning was performed on a 3T MRI. PVSAT (Paced visual serial addition test) was applied as a cognitive task. All functional data was analyzed with SPM12 and statistical analysis with SPSS 19.0. No statistically significant differences between CI and CP patients were found (p=0.953; p=0.322) on the MFIS and BDI score. Performance on the PASAT in CI patients was 34.07±13.721 for CP patients 46.42±11.453, SDMT performance in the CI patient group was 42.40±9.179 in CP group 57.83±2.552. Between-group analysis revealed increased activations in left Brodmann area (BA) 40 in CP patients with several clusters located in left supramarginal gyrus. Regression analysis showed increased BOLD signal in left BA 40, right BA 40 and left BA 6, associated with higher score on MFIS. Stronger BOLD signal in left BA 31 was associated with lower score on MFIS. Significance level set to p<0.05, FWE. The differences in BOLD activations suggest presence of cortical reorganization in our CP patients. The impact of fatigue on cortical activation during cognitive task is demonstrated by inconformity of activated areas depending on the MFIS score. Our results suggest that activation in BA 40 may represent a mechanism for diminishing fatigue impact on cognitive functioning in CP patients.